INFLUENCER DAN LITERASI KEUANGAN DIGITAL: STUDI EKSPLANATIF PADA AKUN YOUTUBE RAYMOND CHIN - Medo Maulianza; Nur Asni Gani; Muhammad Fathan Azka Ramadhan (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study aims to analyze the influence of exposure to Raymond Chin's YouTube content on the digital financial literacy of Generation Z in Indonesia. This study uses Uses and Gratifications Theory as a theoretical basis, which explains that audiences actively choose media to fulfill their information and knowledge needs. The research approach used is quantitative explanatory with a survey method of 100 Generation Z respondents who have watched Raymond Chin's YouTube content. Data were collected through an online questionnaire and analyzed using descriptive statistics, validity tests, reliability tests, classical assumption tests, and simple linear regression. The results show that exposure to Raymond Chin's YouTube content has a positive and significant effect on the digital financial literacy of Generation Z. The regression results show a coefficient of 0.868 with a significance level of 0.000 (p 0.05). The coefficient of determination (R²) value of 0.553 indicates that 55.3% of the variation in digital financial literacy can be explained by exposure to Raymond Chin's YouTube content. These findings indicate that YouTube-based financial education content can function as an effective informal learning medium to improve Gen-Z literacy. This research highlights the importance of collaboration between the government, educational institutions, and digital content creators in strengthening financial literacy programs in the digital age.Keywords: digital financial literacy, financial influencers, YouTube, Generation Z, Uses and Gratifications Theory.